(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This paper introduces the Mnolahma Nelca effect, discovered when J.B. Le Kervinec attempted to fly a paramotor beyond the Ice Wall and was inexplicably returned. This effect posits a space-time deformation around the terrestrial disc, modeled as a hyperbolic umbilic, which repels any object crossing the Ice Wall’s boundary. This phenomenon is proposed to explain the stable orbits of the sun and moon, and the containment of water on the disc. Anthropological research suggests the effect underlies a Humano-murian rite of passage involving a "leap into the unknown," where adolescents are seemingly propelled into the air and return transfigured. This ritual is linked to the Easter Island birdman legend and the widespread mythology of angels. The knowledge of this effect by the Humano-murians is also suggested as a potential origin for the concept of a dome or firmament surrounding the terrestrial disc.